Preferensi Pemilihan Susu Formula Bayi 0-6 Bulan dengan Metode AHP (Analytic Hierarchy Process) - Nisa Ayunda (Publikasi Indonesia, 2021)
In the world of mothers, the selection of formula milk as a substitute or companion for breast milk is very important because good nutrition is needed to support the baby's growth period. Meanwhile, now there are many choices of formula milk that have various benefits for each brand that are tailored to the needs of babies. Seeing these problems, this study offers a solution for choosing infant formula using the AHP (Analytic Hierarchy Process) method. In this study, the selection of formula milk was determined as a goal that looked at 4 criteria of carbohydrates, protein, fat, and calcium and used 11 brands of formula milk as an alternative. By carrying out the stages of completion using the Analytic hierarchy process AHP method, it was found that Organic Baby & Me milk was milk with the highest reference level of 43%.